NLRP3 Inflammasome: A Possible Link Between Obesity-Associated Low-Grade Chronic Inflammation and Colorectal Cancer Development - Patricia Ahechu; Gabriel Zozaya; Pablo Martí; José Luis Hernández-Lizoáin; Jorge Baixauli; Xabier Unamuno; Xabier Unamuno; Gema Frühbeck; Gema Frühbeck; Gema Frühbeck; Gema Frühbeck; Victoria Catalán; et al. (Frontiers in Immunology, 2018)
Emerging evidence reveals that adipose tissue-associated inflammation is a main mechanism whereby obesity promotes colorectal cancer risk and progression. Increased inflammasome activity in adipose tissue has been proposed as an important mediator of obesity-induced inflammation and insulin resistance development. Chronic inflammation in tumor microenvironments has a great impact on tumor development and immunity, representing a key factor in the response to therapy. In this context, the inflammasomes, main components of the innate immune system, play an important role in cancer development showing tumor promoting or tumor suppressive actions depending on the type of tumor, the specific inflammasome involved, and the downstream effector molecules. The inflammasomes are large multiprotein complexes with the capacity to regulate the activation of caspase-1. In turn, caspase-1 enhances the proteolytic cleavage and the secretion of the inflammatory cytokines interleukin (IL)-1β and IL-18, leading to infiltration of more immune cells and resulting in the generation and maintenance of an inflammatory microenvironment surrounding cancer cells. The inflammasomes also regulate pyroptosis, a rapid and inflammation-associated form of cell death. Recent studies indicate that the inflammasomes can be activated by fatty acids and high glucose levels linking metabolic danger signals to the activation of inflammation and cancer development. These data suggest that activation of the inflammasomes may represent a crucial step in the obesity-associated cancer development. This review will also focus on the potential of inflammasome-activated pathways to develop new therapeutic strategies for the prevention and treatment of obesity-associated colorectal cancer development.